Sintesis Teoretis Kompetensi Digital Guru Biologi untuk Penguatan Implementasi Kurikulum Merdeka Melalui Pendekatan Systematic Literature Review - I Gusti Agung Gede Widnyana; Cirtye Labesani; Atika Novince; Delfince Tjenemundan; Melky Alfian; Viskarita F.M Ambotuo (Mathematics Education Study Program, 2025)
This study aims to synthesize findings on teachers' digital competence in the implementation of the Merdeka Curriculum, specifically within the context of biology education. Using a Systematic Literature Review (SLR) methodology, this research analyzes 36 articles discussing the relationship between teachers' digital competence and the success of the Merdeka Curriculum, factors supporting and hindering digital competence development, and the theoretical models used in technology-based learning. The results indicate that teachers' digital competence significantly impacts the success of curriculum implementation, particularly in enhancing technology-based learning and fostering critical thinking among students. Key supporting factors include school leadership, contextual training, and educational policies, while major barriers include limited access to technology and resistance to change. This study proposes an integrated model combining TPACK Framework, Reflective Learning Theory, and Sustainability Pedagogy to strengthen biology teachers' digital competence. The findings contribute to the development of more effective and relevant biology curricula based on technology, aligned with the Merdeka Curriculum.